Pengaruh Kualitas Pelayanan Dan Kemudahan Penggunaan E-wallet Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Tokopedia Di Kemayoran Jakarta Pusat - Hermansyah, Hermansyah; Arwanda Pambudi, Eko (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to determine the extent to which service quality and ease of use of E-wallets influence purchase decisions. This research uses primary data from questionnaires and secondary data from literature. The population of this study includes all Tokopedia consumers using E-wallets in Kemayoran, Central Jakarta. The sample was obtained using Hair's theory, resulting in 145 respondents. The research method employed is a quantitative approach with a descriptive research type. The data analysis techniques used include Descriptive Analysis, Instrument Testing, Classical Assumption Tests, Autocorrelation Tests, Multiple Linear Regression Analysis, T-Tests, F-Tests, Correlation Coefficient Determination, and Determination Coefficient, all conducted using SPSS version 26 software. The research results indicate that there is a significant partial influence of service quality (X1) on purchase decisions (a case study of Tokopedia consumers in Kemayoran, Central Jakarta) (Y) by 41.2%, and a significant partial influence of the ease of use of E-wallets (X2) on purchase decisions (a case study of Tokopedia consumers in Kemayoran, Central Jakarta) (Y) by 54.6%. Based on the F- test results, it is shown that service quality (X1) and ease of use of E-wallets (X2) simultaneously have a significant influence on purchase decisions (a case study of Tokopedia consumers in Kemayoran, Central Jakarta) (Y) by 57.7%, with the remaining 42.3% influenced by other variables not examined in this study.